2021
DOI: 10.1021/acssuschemeng.1c02407
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Self-Assembly of Lytic Polysaccharide Monooxygenase-Oxidized Cellulose Nanocrystals

Abstract: Cellulose-derived nanomaterial building blocks, including cellulose nanocrystals (CNCs), have become increasingly important in sustainable materials development. However, the preparation of CNCs requires hazardous chemicals to introduce surface charges that enable liquid crystalline phase behavior, a key parameter for obtaining self-organized, nanostructured materials from CNCs. Lytic polysaccharide monooxygenases (LPMOs), oxidative enzymes that introduce charged carboxyl groups on their cleavage sites in aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The approach of producing cellulose nanomaterials using LPMO oxidation of cellulose hierarchies has been applied to prepare carboxylated CNCs from microcrystalline cellulose with C1-oxidizing NcLP-MO9E that has a CBM1 (Koskela et al, 2021). The carboxylated CNC product contained a higher carboxyl group content than in our work, at 0.40 ± 0.07 mmol/g.…”
Section: Carboxyl Group Content Of Cncs and Decncsmentioning
confidence: 77%
See 1 more Smart Citation
“…The approach of producing cellulose nanomaterials using LPMO oxidation of cellulose hierarchies has been applied to prepare carboxylated CNCs from microcrystalline cellulose with C1-oxidizing NcLP-MO9E that has a CBM1 (Koskela et al, 2021). The carboxylated CNC product contained a higher carboxyl group content than in our work, at 0.40 ± 0.07 mmol/g.…”
Section: Carboxyl Group Content Of Cncs and Decncsmentioning
confidence: 77%
“…However, proofs of concept for other applications have also emerged. LPMO9s (alone or in combination with cellulases and xylanases) have been demonstrated to produce and oxidize cellulose nanomaterials (Villares et al, 2017;Hu et al, 2018;Moreau et al, 2019;Koskela et al, 2019;Karnaouri et al, 2020;Koskela et al, 2021;Muraleedharan et al, 2021;Rossi et al, 2021;Marjamaa et al, 2022;Magri et al, 2022;Chorozian et al, 2022). In addition, a family AA10 celluloseactive LPMO of bacterial origin has been used to carboxylate cellulose fibers and nanocrystals (Solhi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Here we have optimized a chemo-enzymatic method, based on the unique activity of C1-oxidising LPMOs, to activate cellulose surfaces for further functionalisation. Our study builds upon significant efforts on the kinetic and mechanistic characterisation of LPMOs, 51 recent examples of the use of cellulolytic LPMOs for nanocellulose production, [59][60][61][62][63][64][65] and the development of LPMO assays based on surface carboxylation. 66,92,93 In particular, seminal work by Hsieh and colleagues specifically demonstrated the potential of a chitinolytic LPMO for the chemo-enzymatic functionalisation of insoluble chitin.…”
Section: Discussionmentioning
confidence: 99%
“…52–58 On the other hand, recent research has demonstrated that the ability of LPMOs to disrupt fibre structure under controlled conditions can be used to generate oxidised nanofibrils for materials applications. 59–65 These latter studies exemplify the use of LPMOs to modify the bulk properties of cellulosic materials. However, the potential of LPMOs to surgically introduce carboxylic acid groups on the cellulose surface for subsequent chemical functionalization is relatively unexplored.…”
Section: Introductionmentioning
confidence: 95%
“…The released soluble cello-oligosaccharides were quantified as glucose-equivalents with a phenol–sulphuric acid assay according to a previously reported method. 65…”
Section: Methodsmentioning
confidence: 99%